INOVASI DALAM ORGANISASI PENDIDIKAN MELALUI PENDEKATAN STRATEGIS DAN IMPLIKASINYA TERHADAP KUALITAS PEMBELAJARAN - Suprihatin; Rahmi Susanti; Siti Dewi Maharani; Yenni Anwar (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to reveal the pattern of findings from twenty scientific articles that discuss innovation in educational organizations through a strategic approach and its implications for learning quality. The analysis shows that successful educational innovation is supported by strategic leadership, supportive institutional policies, and adaptive organizational culture. In addition, the incentive system, evaluation of innovative potential, as well as technology integration and cross-sector collaboration are determining factors in the sustainability of innovation. A well-designed strategic approach enables educational institutions to respond to external dynamics, strengthen competitiveness and improve the effectiveness of teaching and learning. The findings confirm that strategy and innovation are two inseparable elements in building resilient and relevant education quality in the global era.